Stability of the LiBH4/CeH2 Composite System Determined by Dynamic pcT Measurements - Mauron, Philippe; Bielmann, Michael; Remhof, Arndt; Zuettel, Andreas; Shim, Jae-Hyeok; Cho, Young Whan (American Chemical Society, 2010)
We determined the stability of the LiBH4/CeH2 composite system by dynamic pcT (pressure, composition, temperature) measurements by using different constant hydrogen flows and by extrapolating In(p(des)/p(0)) linearly to equilibrium at zero flow. During desorption, the reaction 6LiBH(4) + CeH2 -> 6LiH + CeB6 + 10H(2) occurs, leading to a theoretical hydrogen capacity of the destabilized system of 7.4 mass %. Within the model used and by applying the Van 't Hoff equation, the following thermodynamic parameters were determined for the desorption: enthalpy of reaction Delta H-r = (58 +/- 3) kJ mol(-1) H-2 and entropy of reaction Delta S-r = (113 +/- 4) J K-1 mol(-1) H-2, leading to a decomposition temperature T-dec = (240 +/- 32) degrees C at a hydrogen pressure of p(0) = 1.01325 bar, compared with Delta H-r = 74 kJ mol(-1) H-2 and Delta S-r = 115 J K-1 mol(-1) H-2 (T-dec= 370 degrees C) for pure LiBH4.(1)
Keywords: REACTIVE HYDRIDE COMPOSITES; HYDROGEN STORAGE MATERIAL; METAL-BOROHYDRIDES; REVERSIBILITY; DECOMPOSITION; KINETICS; TI